BEBERAPA CATATAN TERHADAP TINDAK PIDANA PASAR MODAL SEBAGAI BAGIAN DARI TINDAK PIDANA EKONOMI - Hasbullah F. Sjawie (Faculty of Law - Tarumanagara University, 2017)
Capital market is a one way to develop size of economic a nation. Through capital market, business can improve, and the fund from investor is accepted by the law without bureaucracy procedure. As investor a shareholder who hold share in a perseroan terbatas terbuka (Indonesia public company limited by share) could by and sell share every time. To keep the stability of the capital market the implementation of openness principle is needed. The Law No. 8 Year 1995 about Capital Market has arranged 3 (three) crime in the capital market. The belief of the public is depending on the disclosure prinsip. It can also be influenced by the violation of capital market law. There are some notes in the regulation. Key words: Capital Market, fraud, market manipulation, insider trading